Politicization of Senior Civil Servants in Slovenia - Lea NAHTIGAL; Miro HAČEK (Transylvanian Review of Administrative Sciences, 2013)
In the context of the civil service system reform, the new normative framework adopted in 2002 introduced a new management arrangement in public administration, whose consequence was the transition of senior positions within ministries, bodies within ministries, and government offices from political officials to positional civil servants with a limited term of office, who have thus become the most senior civil servants, called administrative managers. Based on extensive empirical research and statistical data, this article provides an in-depth analysis of the status and position of administrative managers, which is intended to serve as a test whether the apex of the Slovenian administrative system is politicized and in what form. In the so-called new democracies, politicization most often is manifested as a violation of the principles of political neutrality characteristic of a professional civil service, through personalized and biased appointments of senior civil servants and in the low degree of protection against lay-offs of civil servants on political grounds. Administrative managers thus often have to decide between political susceptibility and trustworthiness versus professionalism and professional accountability, for their tasks belong to the administrative and political realms. This poses a question about the degree of influence politicians exert on administrative managers and the rate of success with which administrative managers manage to retain their professionalism and independence, which should represent the key characteristics of a senior civil servant.